Multimetal removal in aqueous medium using a potato starch/nopal mucilage copolymer: A study of adsorption kinetics and isotherms - Choque Quispe, David (2023)
In reducing heavy metals from water for direct or indirect consumption, various synthetic materials have been used; there is a tendency to use natural, biodegradable, and environmentally friendly materials. The aim was to elaborate copolymers with native potato starch and cactus mucilage and evaluate water’s multimetal removal capacity. The copolymer was characterized, and the kinetics and adsorption isotherms were evaluated. The copolymers presented high solubility for nopal mucilage levels of 5% w/w, with particle size in aqueous solution less than 422.83 nm, zero charge point around pH 5.5, and potential between 16.72 and 29.80 mV; FTIR analysis showed the predominance of anionic groups with chelating capacity. Multimetal adsorption was from 102.20 to 151.43 mg/g, with affinity in the order Pb > As > Al > Hg > Cr, being higher at pH 6 (p-value<0.05). Kinetic data were fitted to the PSFO, PSSO, and Elovich models with R2>0.994, X2<16.098, ARE<34.038, and random residual dispersion, indicating a chemisorption process. The adsorption isotherms were adjusted to the Langmuir, Freundlich, and Redlich-Peterson models with R2>0.863, whose parameters are related to the ionic radius of the metals, with favorable adsorption and a heterogeneous surface of the copolymer. The mean adsorption energy was found between 0.05 and 0.23 kJ/mol. The use of native potato starch and cactus mucilage allows the formulation of copolymers with high multimetal adsorption potential in aqueous systems.